2008
DOI: 10.1158/1078-0432.ccr-07-1605
|View full text |Cite
|
Sign up to set email alerts
|

Overall and Relapse-Free Survival in Oropharyngeal and Hypopharyngeal Squamous Cell Carcinoma Are Associated with Genotypes of T393C Polymorphism of the GNAS1 Gene

Abstract: Purpose: In previous studies, we have shown that theTallele of a specific single-nucleotide polymorphism (SNP) in the Gas gene (T393C) correlates with increased Gas expression and hence apoptosis. The T allele was associated with a favorable outcome in a variety of human cancers, e.g., carcinoma of the urinary bladder, kidney, and colorectum. Experimental Design: The prognostic value of theT393C SNP was evaluated in an unselected series of patients treated with curative intent for oropharyngeal and hypopharyng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…6). Thus, XL␣s extended the duration of the cAMP response induced by the typically short acting agonist M-PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Although this finding was consistent with the absence of XL␣s internalization upon activation, a similar effect was not observed when the same cells were stimulated by isoproterenol.…”
Section: Conserved Cysteine Residues and A Region Comprising Hcd (Butmentioning
confidence: 57%
See 1 more Smart Citation
“…6). Thus, XL␣s extended the duration of the cAMP response induced by the typically short acting agonist M-PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Although this finding was consistent with the absence of XL␣s internalization upon activation, a similar effect was not observed when the same cells were stimulated by isoproterenol.…”
Section: Conserved Cysteine Residues and A Region Comprising Hcd (Butmentioning
confidence: 57%
“…We addressed this hypothesis by using a Förster resonance energy transfer (FRET)-based reporter that permits real time recording of cAMP production in live cells (46). As an agonist, we chose a PTH analog, M-PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), which has been shown to induce a short lived cAMP response (41). As expected, a rapid change in the FRET signal was observed upon the addition of 100 nM M-PTH (1-14) onto HEK293 cells expressing the PTHR alone or in combination with XL␣s and G␤ 1 ␥ 2 (Fig.…”
Section: Conserved Cysteine Residues and A Region Comprising Hcd (Butmentioning
confidence: 99%
“…Oro-and hypopharyngeal squamous cell carcinoma [16] 2008 202 C homozygous patients displayed a higher risk for disease progression than T homozygous patients (P = 0.019) and a higher risk for death (P = 0.015). In multivariate analysis, besides cancer stage and tumor localization, the T393C polymorphism was an independent prognostic factor for disease progression and death…”
Section: Tt-genotypementioning
confidence: 98%
“…Previous studies indicate that increased expression of Gαs enhances apoptosis [7,8] and that Gαs mRNA expression is different between T393C genotypes [9] . For various solid tumors, previous studies demonstrated that patient survival and tumor progression depended on T393C genotype [10][11][12][13][14][15][16][17] . Until now, nothing has been published about the impact of the GNAS1 T393C polymorphism on gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic polymorphisms are considered to be molecular markers that predict the risk, progression and prognosis of various cancers (3)(4)(5)(6)(7). Indeed, single nucleotide polymorphisms (SNPs) in several genes are reported to be associated with the risk of lung cancer (8)(9)(10), for example SNPs in the caspase-3 and vascular endothelial growth factor genes (11,12).…”
Section: Introductionmentioning
confidence: 99%